Pilot-scale drying of southern pine (Pinus spp.) lumber in a heated tube dryer - Shmulsky R; Khademibami L; Rezaei F (iForest - Biogeosciences and Forestry)
Drying is essential for preserving the strength and durability of wood and wood products. This study aimed to evaluate the performance of a pilot-scale tube-type lumber dryer. Solid sawn rough green southern yellow pine (Pinus spp.) specimens, approximately 2 inches thick by 6 inches wide, and 12 feet long (≈ 5 cm × 15 cm × 3.66 m), were inserted into heated tubes for drying. The pilot scale dryer had four sealed (but open at each end) steel heated tubes, and each tube was sized to hold four specimens. Each tube was 36 ft (≈11 m) long. The temperature of the tube was controlled by rapidly circulating hot air about the tubes’ exterior. Each tube had 3 temperature zones, and each temperature zone was controlled individually. Each lumber specimen was inserted into zone 1 and dried for a specified amount of time, and then advanced to zone 2 and zone 3. The delta moisture content of dried specimen was calculated based on the initial and final weight and final moisture content. The results showed that the delta moisture content was greatest at 425-425-400 °F (≈218-218-204 °C) and lowest at 400-400-350 °F (≈204-204-177 °C). Greater weight-loss rates were observed in the dried lumbers within the temperature range of 375-375-375°F (≈191-191-191 °C). In summary, this device rapidly dried the lumber, and moisture content standard deviations were relatively high.